Unlocking Loyalty: The Power of Halal Labels on Customer Satisfaction and Purchasing Decisions - Lestari, Putri; Budiman, Andika Nuraga (Research of Islamic Economics, 2025)
This research was conducted with the aim of testing the effect of the halal label on customer loyalty through purchasing decisions and customer satisfaction as mediating factors. This research was designed as explanatory research. The sampling technique used was non-probability sampling. Data collection was carried out using a questionnaire survey instrument method via the Google Form page. The researfactor: lts show that the halal label has a positive and significant effect on customer loyalty; customer satisfaction has no effect on customer loyalty; the influence of the halal label on customer loyalty is not mediated through customer satisfaction as a mediating factor; Purchasing decisions can partially mediate the relationship between halal labels and customer loyalty. Managerial Implications This research shows that the halal label has a significant impact on customer loyalty and purchasing decisions, with customer satisfaction acting as an important intervening variable. The role of intervening variables in this research plays a key role in explaining how the relationship between independent variables and dependent variables can occur indirectly through these variables. In the context of this research, the independent variable is the halal label, while the dependent variable is customer loyalty.